2019
DOI: 10.1080/1331677x.2019.1675079
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of cost accounting as the economic pillar of management accounting systems in public hospitals – the case of Slovenia and Croatia

Abstract: Healthcare sector expenditures persistently rise due to various public health, demographic, and socio-cultural reasons. This fact caused repeated calls for reforms of the economic model in the healthcare sector due to increased concern for efficiency. The aim of this paper is the comparison of the Slovenian and Croatian healthcare systems, focusing mainly on the current development stage and the future challenges of the management (cost) accounting systems. The research is mainly interested in the analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
(79 reference statements)
0
9
0
1
Order By: Relevance
“…In a similar vein, other studies uncovered insignificant change in hospital management accounting practices (see for instance Fahlevi, 2016). These studies show that many hospitals across the globe are still using traditional costing and cost management that are too aggregate and incapable of tracking cost per patient (see for instance, Rauliajtys-Grzybek et al, 2017;Jovanovi c et al, 2019). Meanwhile, several prior studies, for instance in Finland, Italy and France, found the support of physicians for cost management and relatively more successful MACs in hospitals (For instance, Lehtonen, 2007;Fiondella et al, 2019;Flachère, 2014).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a similar vein, other studies uncovered insignificant change in hospital management accounting practices (see for instance Fahlevi, 2016). These studies show that many hospitals across the globe are still using traditional costing and cost management that are too aggregate and incapable of tracking cost per patient (see for instance, Rauliajtys-Grzybek et al, 2017;Jovanovi c et al, 2019). Meanwhile, several prior studies, for instance in Finland, Italy and France, found the support of physicians for cost management and relatively more successful MACs in hospitals (For instance, Lehtonen, 2007;Fiondella et al, 2019;Flachère, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…Second, doctors are encouraged to standardise and evaluate the use of a mix of resources for treating each patient and DRG case. In other words, the costing approach needs to be transformed into a system that would enable the provision of a comprehensive financial calculation of costs of both individual patient treatment and individual DRG case (Lehtonen, 2007;Jovanovi c et al, 2019). Such a more detailed and individual costing approach is called casemix accounting (Lehtonen, 2007;Leotta and Ruggeri, 2017).…”
Section: Diagnosis-related Groups-based Payment System and Management...mentioning
confidence: 99%
“…In the past, there have been attempting to standardize solutions in this area at the national level, as well as there have been demands for the use of more modern solutions, for example in the form of activity cost accounting (Chluska, 2007). These problems do not only concern the Polish healthcare system (Jovanović, Dražić-Lutilsky, Vašiček, 2019).…”
Section: Standard Of Cost Accounting In Healthcare Entitiesprinciples...mentioning
confidence: 99%
“…Setiap kegiatan dalam ma syarakat harus melibatkan seluruh warga nya, sehingga tidak ada yang merasa diting galkan, semua harus bersatu padu dalam kebersamaan. Memiliki rasa persaudaraan yang kuat akan membangun rasa persatuan sehingga keikhlasan dalam tolong menolong di antara warga masyarakat melahirkan sifat gotong royong yang merasuk ke dalam sa nubari (Hermawan, 2013;Jovanović et al, 2019;Zeidan & Khumawala, 2014). Pasien, tenaga medis, rumah sakit, fasilitas kesehat an, pemerintah, dan BPJS Kesehatan harus menjadi satu kesatuan sehingga tujuan JKN dapat tercapai.…”
Section: Rugi Pokok E" (Tarniunclassified